1998
DOI: 10.1097/00007890-199808270-00004
|View full text |Cite
|
Sign up to set email alerts
|

T Cells in Islet-Like Cell Cluster Xenograft Rejection

Abstract: In the pig-to-mouse model, fetal porcine ICC xenograft rejection is exclusively dependent on T cells bearing TCR-alphabeta chains. In addition, the absence of perforin or GraB has no influence on the rejection process, suggesting that xenospecific cytolytic T cells are of minor importance. Even if TNF-alpha is of importance to the developing process of ICC xenograft rejection, other cytokines, i.e., interferon-gamma, might efficiently substitute for the lack of TNF-alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Conventional wisdom has suggested that T cells are recruited to the graft via secondary lymphoid organs. Once they have reached the graft, they provide the signals necessary for ongoing macrophage recruitment (26). However, in our model, an alternative mechanism for macrophage involvement has been proposed.…”
Section: Discussionmentioning
confidence: 90%
“…Conventional wisdom has suggested that T cells are recruited to the graft via secondary lymphoid organs. Once they have reached the graft, they provide the signals necessary for ongoing macrophage recruitment (26). However, in our model, an alternative mechanism for macrophage involvement has been proposed.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, recent data obtained in our laboratory have shown that animals in which major parts of the TH1-associated cytokine pathway, namely interferon-? and IL-2 [38] or tumor necrosis factor-a [3], have been blocked, readily reject fetal porcine ICC xenografts. Taken together, it might be speculated that the rejection process of an ICC xenograft induces a vast immune response consisting of both TH1-and TH2-related components.…”
Section: Discussionmentioning
confidence: 99%
“…1 and Tables 1-3. Fetal porcine ICCs were transplanted under the kidney capsule as previously described (17). One week to Ͼ1 year before transfer, recipient athymic (nu/nu) mice received an implant of either 3 l of fetal porcine ICC alone (Tables 1 and 3) IH, immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…X0902; Dako A/S, Glostrup, Denmark) for 10 min. Immunohistochemical stainings using rat anti-mouse monoclonal antibodies to F4/80, Mac-1, MHC class II, CD3, CD8 (Serotec, Kidlington, U.K.), and CD4 (Pharmingen, San Diego, CA) were performed as previously described (17). The slides were counterstained with hematoxylin and mounted in glycerine gelatin.…”
Section: Methodsmentioning
confidence: 99%